A Systems Integration Approach to an Instrumented Tidal Energy Converter within an Open-Source Testbed (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Tidal energy converters (TEC), e.g., marine hydrokinetic turbines, harness the kinetic energy of tidal currents to generate clean renewable power. The Open-Source Tidal Energy Converter (OSTEC) project will design, build, and deploy an instrumented marine turbine system in a real tidal environment and will serve as a testbed for research and development. With its 2.5 m rotor diameter and 26 kW rated power, this tidal turbine will generate open-source datasets on power performance, mechanical and design loads, and tidal inflow conditions at meaningful Reynolds number scales.Many studies have focused on the system integration of TECs with other infrastructure, such as electrical grids, farms, or hybrid energy systems. This contribution focusses on the evolution and system integration of the first-of-its-kind OSTEC itself, replicating the systematic approach of design, prototyping, and testing commonly used in industries that develop large complex systems, like the aerospace industry, paving the way for industrial and commercial-scale devices.System integration combines different assemblies, sub-assemblies, and components of a system into one cohesive whole. The objective for OSTEC is to systematically coordinate the testing, connection, and assembly of individual components, sub-assemblies, and the complete system. This process ensures that all elements function as specified at various integration levels and work seamlessly together to meet the system’s design criteria and achieve the project's goals.The sequence and interdependencies of testing, assembly, and system integration for the OSTEC turbine are planned collaboratively by the Atlantic Marine Energy Center at the University of New Hampshire, Sandia National Laboratories, the National Renewable Energy Laboratory, and Pacific Northwest National Laboratory.The OSTEC turbine comprises two principal subsystems: a three-bladed, highly instrumented axial-flow hydrokinetic turbine designed to convert hydrokinetic energy into electrical power, and a data acquisition (DAQ) subsystem for measuring and recording critical parameters.The OSTEC system integration involves multiple parallel tasks. A liftable rack will accommodate the power electronics and PTO controls, which will be integrated into a UNH-designed adaptation of the NREL Modular Ocean Data Acquisition (MODAQ) system. MODAQ will also serve as the primary health monitoring system for the turbine on monitoring water intrusion, sensor faults, overload conditions, etc. as well as turbine control setpoint. To synchronize clocks throughout the DAQ network, a precision time protocol (PTP) scheme is utilized. Additionally, a custom-built test and assembly stand streamlines the integration process.The turbine system, equipped with numerous sensors, will generate extensive data during deployment. After precise testing and integration, a dry test will verify mechanical integrity and component functionality, followed by a leak test. The system will then be prepared for deployment at the UNH Pier, where the Turbine Deployment Platform will also undergo modifications for OSTEC installation.In summary, system integration aims to optimize system integrity, reliability, efficiency, operation, and lifecycle by seamlessly integrating various components, controls, and infrastructure. It requires multidisciplinary expertise in mechanical engineering, electrical engineering, control systems, and project management. This contribution provides an overview and update on the system integration of the instrumented OSTEC testbed, planned for deployment in summer 2025.